PERAN SITI WALIDAH DIBIDANG PENDIDIKAN DAN SOSIAL DALAM PERKEMBANGAN AISYIYAH TAHUN 1917-1946 - Ika Setiya Wati; Ragil Agustono (Swarnadwipa, 2017)
Problems in this research The role of Siti Walidah in the field of education and social to promote education and improve the dignity of women. The method used in this research is the historical method by conducting literature study. Data collection techniques in this study using heuristic steps and literature study. In testing the truth of a data or validity of data collection used internal and external critic, while for data analysis method is by interpretation and historiography. The results of this study are:The role of Siti Walidah in the field of education in an effort to realize and advance education) including those who succeed in their business in the field of education is not only a theory, but actively proven to educate indigenous women of the 20th century and promote the religious education of women in the educational process. Done by Siti Walidah is held dormitory daughter-daughter from various regions in Indonesia, Siti Walidah actively assist the smooth implementation of the girls schools and then educate the women through the course and conduct pengajian of Islam and participate in the eradication of illiteracy.The role of Siti Walidah in the social field is to play an active role in the development and empowerment of the potential of women and increase the dignity of women. Siti Walidah builds and develops the potentials of women so that they are active in the development of activities as well as in the orphanage builder named Putri Aisyiyah and help the poor, orphans to make an activity within the community.